"Shwatsit!" : no one knows just what it means - Ditchfield, Christin (Golden Book, 2009)
"As Baby points at everything in sight, she has just one thing to say: 'Shwatsit!' But what on earth does it mean? Finally, her older brother solves the mystery while watching her try to reach for her teddy bear"--Publisher.